Elective node irradiation with integrated boost to the prostate using helical IMRT: clinical outcome of the prospective PLATIN-1 trial - Körber, Stefan A.; Winter, Erik; Katayama, Sonja; Slynko, Alla; Häfner, Matthias; Uhl, Matthias; Sterzing, Florian; Habl, Gregor; Schubert, Kai; Debus, Jürgen; Herfarth, Klaus (Frontiers in oncology, 2019)
Introduction: This prospective, non-randomized phase II trial aimed to investigate the role of additional irradiation of the pelvic nodes for patients with prostate cancer and a high risk for nodal metastases using helical intensity-modulated radiotherapy with daily image guidance (IMRT/IGRT). Methods and materials: Between 2009 and 2012, 40 men with treatment-naïve prostate cancer and a risk of lymph node involvement of more than 20% were enrolled in the PLATIN-1 trial. All patients received definitive, helical IMRT of the pelvic nodes (total dose of 51.0 Gy) with a simultaneous integrated boost (SIB) to the prostate (total dose of 76.5 Gy) in 34 fractions. Antihormonal therapy (AHT) was administered for a minimum of two months before radiotherapy continuing for at least 24 months. Results: After a median follow-up of 71 months (range: 5 - 95 months), pelvic irradiation was associated with a 5-year overall survival (OS) and biochemical progression-free survival (bPFS) of 94.3% and 83.6%, respectively. For our cohort, no grade 4 gastrointestinal (GI) and genitourinary (GU) toxicity was observed. Quality of life (QoL) assessed by EORTC QLQ-C30 questionnaire was comparable to EORTC reference values without significant changes. Conclusion: The current trial demonstrates that elective IMRT/IGRT of the pelvic nodes with SIB to the prostate for patients with a high-risk of lymphatic spread is safe and shows an excellent clinical outcome without compromising the quality of life. The PLATIN-1 trial delivers eminent baseline data for future studies using modern irradiation techniques.